Physiological Responses and Metabonomics Analysis of Male and Female Sargassum thunbergii Macroalgae Exposed to Ultraviolet-B Stress - Sun, Yan; Liu, Qian; Shang, Shuai; Chen, Jun; Lu, Peiyao; Zang, Yu; Tang, Xuexi (Frontiers in Plant Science, 2022)
Ultraviolet-b (UV-B) radiation is a major environmental stress that suppresses or activates defense responses in plants. UV-B radiation affects growth and development in plants, but a series of unknown knowledge remain in the male and female algaes comparison. To investigate the metabolic responses of the Sargassum thunbergii (S. thunbergii) algae to UV-B irradiation, the method of metabolomic analysis have been performed in our experiments. Levels of specific metabolites were measured, including soluble sugar, soluble protein, and lipid. The untargeted metabolomics analysis revealed that exposure to enhanced UV-B irradiation significantly affected carbon and nitrogen metabolism in female and male S. thunbergii. Based on experimental measurement, the contents of soluble sugar, soluble protein and total lipid increased slightly under low UV-B radiation. Under high UV-B radiation, the content of soluble sugar and total lipid decreased significantly, and the content of soluble protein increased. Between diecious algaes, the soluble sugar and soluble protein of male algae were significantly higher than those of female algae, and the lipids content was significantly reduced. Our results demonstrated that UV-B radiation altered biomass allocation between diecious S. thunbergii and different physiological responses which might help S. thunbergii to reduce the damages under UV-B stress. This study linked the method of metabonomics analysis, carbon metabolites allocation and sex-differential S. thunbergii comparison, provided new insights and fundamental knowledge in the research of relationship between diecious macroalgae and intertidal ecosystems.